Urine/Plasma Neutrophil Gelatinase Associated Lipocalin Ratio Is a Sensitive and Specific Marker of Subclinical Acute Kidney Injury in Mice. - Tamás Kaucsár; Mária Godó; Csaba Révész; Miklós Kovács; Attila Mócsai; Norbert Kiss; Mihály Albert; Tibor Krenács; Gábor Szénási; Péter Hamar (PLoS ONE, 2016)
BACKGROUND:Detection of acute kidney injury (AKI) is still a challenge if conventional markers of kidney function are within reference range. We studied the sensitivity and specificity of NGAL as an AKI marker at different degrees of renal ischemia. METHODS:Male C57BL/6J mice were subjected to 10-, 20- or 30-min unilateral renal ischemia, to control operation or no operation, and AKI was evaluated 1 day later by histology, immunohistochemistry, BUN, creatinine, NGAL (plasma and urine) and renal NGAL mRNA expression. RESULTS:A short (10-min) ischemia did not alter BUN or kidney histology, but elevated plasma and urinary NGAL level and renal NGAL mRNA expression although to a much smaller extent than longer ischemia. Surprisingly, control operation elevated plasma NGAL and renal NGAL mRNA expression to a similar extent as 10-min ischemia. Further, the ratio of urine to plasma NGAL was the best parameter to differentiate a 10-min ischemic injury from control operation, while it was similar in the non and control-operated groups. CONCLUSIONS:These results suggest that urinary NGAL excretion and especially ratio of urine to plasma NGAL are sensitive and specific markers of subclinical acute kidney injury in mice.